(untitled) (Research, Society and Development, 2022)
Studies on Organizational Behavior (OC) have significantly contributed to the consolidation of administration as a science and the managerial development of organizations. The construction of theories, the foundation of analysis and the understanding of people’s behavior in organizations are fundamental elements for the construction of knowledge in this area. The objective of this work was to portray the last 10 years of the evolution of the CO field in Brazil, based on the systematic survey, analysis and critical evaluation of the scientific production in the period from 2011 to 2020, based on a documentary research in the main journals of Administration . Results showed that the researchers focus on qualitative research, while the approach was divided almost equally between survey, bibliographic research and case studies, and questionnaires and documental research are the most used means of data collection. It is concluded that more and more interest in publishing on the subject is lost, since there was a decrease in the number of publications from the middle of the decade.